Amphiphilic sugar poly(orthoesters) as pH-responsive nanoscopic assemblies for acidity-enhanced drug delivery and cell killing1. Issue 66 (25th August 2015) - Li, Lingyao; Knickelbein, Kyle; Zhang, Lin; Wang, Jun; Obrinske, Melissa; Ma, Gene Zhengxin; Zhang, Li-Ming; Bitterman, Lindsay; Du, Wenjun
<x xml:space="preserve">Abstract</x> A sugar poly(orthoester)-based drug delivery system was constructed to achieve acidity-enhanced drug delivery and cell killing.